Iraqi Women with Preeclampsia: Maternal and Neonatal Outcomes - Abdulhameed Majeed, Ban; Kadhim Jasim, Shaymaa; Al-Momen, Hayder; Hussein, Mohammed Jalal (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Preeclampsia (PE) is a possible etiology of obstetrical and neonatal complications which are increased in resource-limited settings and developing countries. AIM: We aimed to find out the prevalence of PE in Iraqi ladies and specific outcomes, including gestational weight gain (GWG), cesarean section (CS), preterm delivery (PD), and low birth weight (LBW). METHODS: All singleton pregnant women visiting our tertiary center for delivery were involved over 3 years. PE women were compared with non-PE ladies. Complete history and examination were done during pregnancy and after delivery by the attending obstetrician and neonatologist with full documentation in medical records. RESULTS: PE prevalence was 4.79%, and the affected women had significant (p < 0.05) higher age, body mass index, and GWG, but lower gestational age at delivery. The mean significant difference of GWG in PE and non-PE patients was 1.82 kg. PD and LBW had significant higher frequencies in PE. After considering several confounding factors, crude and adjusted odds ratio (OR) of PE with 95% confidence interval (95% CI) were significant in CS (crude OR = 2.25 and 95% CI = 1.42-2.87 while adjusted OR = 2.89 and 95% CI = 1.43–3.06) and PD (crude OR = 2.41 and 95% CI = 1.73–2.46 while adjusted OR = 3.96 and 95% CI = 2.65–6.37). On the other hand, only the crude model touched significance in LBW (crude OR = 3.67 and 95% CI = 2.51–4.99). CONCLUSIONS: Prevalence of PE in Iraqi pregnant females was higher than other neighboring developing countries. In PE ladies, maternal parameters, including GWG and operative delivery, and neonatal complications, including PD and LBW, were significantly higher than pregnant women without PE.